The game with “the death” in Ian McEwan’s novel “Amsterdam” - Гура, Наталя Петрівна; Іваніків, Людмила Ігорівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article deals with the motive of death in Ian McEwan’s novel  “Amsterdam”. Analyzing the decline of idealism and the moral degradation of society at the turn of the centuries, the British writer refers to such basic categories of being as life and death. It was the death became the leitmotiv of the novel and an integral part of his poetics. The author prepares human nature gracefully and skillfully, showing the vices, shortcomings and basic instincts. Significant attention is paid to the transformation of the novel leitmotiv: under the influence of postmodern aesthetics, death transforms into euthanasia, which then turns out to be a double murder.